A new Phanerothecium (Monopisthocotyla, Oogyrodactylidae) species parasitizing Hypostomus strigaticeps (Siluriformes, Loricariidae) in the Pardo River, Southeastern Brazil - Silva, Rafael Augusto Pereira da [UNESP]; Aguiar, Julio Cesar Cenci de [UNESP]; Ebert, Mariana Bertholdi; Silva, Reinaldo José da [UNESP] (Springer Nature, 2025)
Phanerothecium acutumsp. n., the eighth described species of the genus Phanerothecium, is characterized by a unique combination of morphological and molecular traits. Morphologically, it differs from closely related species such as P. spinatus, P. deiropedeum, and P. macrosomum by features of the male copulatory organ (MCO), anchor configuration, and ventral bar structure. Notably, P. acutumsp. n. possesses an MCO armed with delicate spines, robust and truncated anchors with a slight elevation on the shaft, and a ventral bar with expanded extremities. Molecular analyses yielded three new 18S and two partial 28S rDNA sequences. A newly developed primer (DAC18F2) markedly improved PCR success and sequencing quality for 18S amplification. Genetic distance analyses based on 18S support P. acutumsp. n. as a distinct species, with interspecific divergence from most congeners ranging from 1.4–2.0%, and intraspecific variation of 0.0–0.2%. However, its genetic similarity to Phanerothecium sp. KX981456 (0.2–0.9%) highlights the need for additional data to clarify species boundaries. Phylogenetic reconstructions based on 18S and 28S confirmed the monophyly of Phanerothecium, placed within a strongly supported clade alongside viviparous gyrodactylideans, and reaffirmed the validity of the family Oogyrodactylidae. These findings underscore the importance of integrative approaches for resolving taxonomic relationships and suggest that the genus Phanerothecium, particularly among loricariid hosts, harbors greater diversity than currently recognized.